Análisis e interpretación de los estados financieros, como herramienta para la evaluación de la gestión empresarial - Correa Correa, Maritza Carolina (2015)
The present work of qualification is based on the analysis and interpretation of financial statements due to the importance they have take in the present, since the financial analysis helps us to determine the current status of the commercial entity through its main tools financial indices or also known as ratios thus facilitating the decision-making and projecting to the future, the development liquidity, solvency, indebtedness for this is thoroughly analyzed financial information , the methodology used was based on method of scientific research descriptive methodology, methodology perspective be guided by observation , surveys, interview.